Reducing roof bolter operator cumulative trauma exposure - Ergonomics considerations for reducing cumulative trauma exposure - Kim M. Cornelius (The National Institute for Occupational Safety and Health (NIOSH), 1997)
Musculoskeletal injury is a term used to describe a wide range of soft tissue disorders which affect the nerves, tendons, and muscles. Common examples include lower back pain, tendonitis, and carpal tunnel syndrome. The majority of these injuries are not the result of sudden mishaps, but usually develop gradually from repeated wear and tear. Symptoms may first appear after weeks, months, or even years. Symptoms may result from many types of activities, performed at work or at home, and it is often difficult to attribute a single event. In fact, it is more common to identify the factors which may have contributed to the development of the condition. The terms repetitive strain injuries or cumulative trauma disorders (CTDs) have been commonly used to refer to disorders that have occurred due to work related activities (Putz-Anderson, 1988; Fraser, 1989). Three main risk factors contribute to CTDs: force, repetition, and awkward postures. Any one or combination of these may contribute to the development of CTDs. Therefore, the design of equipment in conjunction with the required tasks should attempt to reduce these risk factors. Examining the layout of the work area to help identify tasks which may contribute to cumulative trauma is necessary. The following list(Putz-Anderson, 1988), describes ergonomic concerns that, overall, should be minimized at the work area: